Effect of phase composition on the parameters of non-isothermal moisture transfer in unsaturated sandy soils - Korolev, Vladimir A.; Fedyaeva, Elena A. (Journal of Civil Engineering and Management, 2014)
This paper considers the influence of phase composition on the parameters of non-isothermal moisture transfer in unsaturated sandy soils. The technique of study options non-isothermal moisture transfer to disperse soil of disturbed structure. The exploratory procedure of the parameters in disperse soils having disturbed structure in the wide range of their phase composition using triangular diagrams is expounded. Shown that the parameters non-isothermal moisture transfer depend on moisture content and soil composition density. Established that for the sandy soil there is the “optimal” range of moisture content and density at which the non-isothermal moisture transfer is most efficient. The dynamics of the field moisture content of sand in time is identified.